Explain the experiences of medical students from running a peer program as a mentor: A qualitative study - sedigheh Najafipour; Tahereh Rahimi; Abazar Roustazadeh; Nima Dadgar; Esmaiel Rayeatdost; Mohammad Rahmanian; Marzeeh Haghbin; Alireza Sadernishin; Zahra Dehdashti; Parisa Pourabbas; Benyamin Omidmokhtarleo; Hamidreza Mortazaveei (Journal of Medical Education and Development, 2022)
Introduction: Today, peer education programs focus on scientific support, guiding and creating interaction between students has been considered to model students' scientific progress. The purpose of this study is to explore the experiences of medical students from implementing the peer program as a mentor using a qualitative framework. Methods: The present study is a qualitative study of the type of contractual content analysis with code of ethics IR.NASRME.REC.1400.067. The participants were selected by purposive sampling method with maximum diversity approach, including 30 medical students and 13 peers as mentors from 94 to 1400 entries. Qualitative data were collected using in-depth semi-structured interviews. The duration of the interviews was between 45-60 minutes. Result: In total, 24 girls (55.8 percent) and 19 boys (44.2 percent) students participated in this study. From the total interviews conducted, 267 open codes, 5 categories and 2 main themes were extracted. The main topics and classes include "Peer as mentor program; a need-based approach" with the sub-themes of facilitating the learning process, accelerating the achievement of goals and developing communication skills, and "The need to promote the peer as mentor program" with the sub-themes of the need to strengthen the infrastructure and the necessity of reviewing the standards related to the selection of the group leader. Conclusion: The findings of the study showed that the process of the peer training program as a mentor is accompanied by challenges, but it can facilitate, increase theoretical and practical learning, as well as develop the communication skills of medical students.